Modified alkali metal anode based on COF in-situ self-assembly artificial SEI layer and preparation method and application thereof

By constructing COF in situ self-assembly artificial SEI layer on alkali metal anode, the problems of scattered COF and low Young's modulus in the prior art are solved, and ultra-long, stable, dendrite-free lithium metal anode and high-efficiency alkali are achieved Metal ion deposition enhances the cyclic stability and interface performance of the battery.

CN119153631AActive Publication Date: 2024-12-17GUANGDONG UNIV OF TECH

Patent Information

Application Number
CN202411029131.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-30
Publication Date
2024-12-17
Estimated Expiration
2044-07-30

AI Technical Summary

Technical Problem

The existing modified COFs are scattered during the preparation of alkali metal anode, with low Young's modulus and compatibility problems leading to phase separation, affecting the performance of the anode material, and making it difficult to form an effective electronic connection, resulting in slow charge transfer at the interface of lithium metal negative electrodes.

Method used

The preparation method of modified alkali metal anode based on COF in situ self-assembled artificial SEI layer is adopted. By constructing the flux of uniform lithium ion deposition, the direct contact between lithium metal and electrolyte is blocked, and COF precursor solution and organic functional solvent are used in alkaline. The metal surface is uniformly coated and dried at low temperature to form an ultra-long, stable, dendrite-free lithium metal negative electrode.

Benefits of technology

It realizes an ultra-long, stable, dendrite-free lithium metal negative electrode, with efficient alkali metal ion deposition and good interfacial performance, and enhances the cell cycle stability and alkali metal ion mobility rate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004969430520000011
    Figure HDA0004969430520000011
Patent Text Reader

Abstract

The invention belongs to the technical field of preparation of nano-composite functional materials, and discloses a modified alkali metal anode based on a COF in-situ self-assembled artificial SEI layer and a preparation method and application of the modified alkali metal anode. The alkali metal anode can effectively and efficiently inhibit dendritic crystal growth and has high Young modulus, and an assembled battery is high in cycling stability and has good alkali metal ion migration rate and good interface performance; the preparation method is simple, the COF layer is synthesized in situ on the surface of the alkali metal through self-deposition assembly of the COF precursor, the COF layer has a rich pore structure and can uniformly induce deposition of alkali metal ions and inhibit growth of dendrites, and the problem that in the prior art, lithium dendrites are easily generated in a negative electrode of an alkali metal battery, so that the performance of the battery is affected is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of preparation of nano-composite functional materials, and in particular relates to an alkali metal anode modified by an artificial SEI layer based on COF in-situ self-assembly, and a preparation method and application thereof. Background Art

[0002] Covalent organic frameworks (COFs), as a new type of crystalline porous organic material, have been gradually developed and applied to the protection of dendrite growth of lithium metal anodes due to their advantages such as designable structure and function, high specific surface area, and stable structure. The ordered pore structure provides a rich migration pathway for the transmission of a variety of high-rate carriers, and the variable chemical environment of the π electron cloud provides a guarantee for the storage and conversion of electrochemical energy.

[0003] Feng et al. developed a COFs coating with maximum lithium affinity and uniform lithium ion flux, which can effectively avoid the formation of lithium dendrites. In addition, the in-situ constructed microporous anionic COFs interface layer can preferentially adsorb and permeate lithium ions, has higher conductivity than liquid electrolytes, and optimizes ion transport. COFs show insulating properties similar to traditional SEI and can effectively mitigate side reactions on the surface of lithium metal anodes. Mainstream SEI designs mainly focus on in-situ or coatings, which rely on high lithium affinity, ionic conductivity, and continuous and stable lithium ion migration. However, it is difficult to form an effective electronic connection between the lithium metal anode and the coating, resulting in slow interfacial charge transfer. Summary of the invention

[0004] In order to overcome the shortcomings and deficiencies of most modified COFs in the prior art, such as being scattered on the surface of alkali metals, having a low Young's modulus, and often prone to phase separation due to compatibility issues during the preparation of the COF layer, which damages the performance of the anode material, or lacking corresponding special structures and atomic clusters that induce uniform deposition of alkali metal ions, the primary purpose of the present invention is to provide a method for preparing an alkali metal anode modified with an artificial SEI layer based on COF in situ self-assembly; the method adopts an in-situ strategy to prepare an artificial COF layer SEI film to achieve an ultra-long stable, dendrite-free lithium metal negative electrode, and is by constructing a flux with uniform lithium ion deposition, based on the in-situ self-assembly of an artificial SEI layer of COF to hinder the direct contact between lithium metal and the electrolyte, thereby preparing an ultra-long stable, dendrite-free lithium metal negative electrode.

[0005] Another object of the present invention is to provide an alkali metal anode modified by an artificial SEI layer based on COF in situ self-assembled by the above-mentioned preparation method; the alkali metal anode has the characteristics of uniformly induced alkali metal ion deposition, can effectively and efficiently inhibit dendrite growth, and has a higher Young's modulus. The assembled battery has strong cycle stability, good alkali metal ion migration rate and good interface performance.

[0006] Another object of the present invention is to provide an application of the above-mentioned COF-based in-situ self-assembled artificial SEI layer modified alkali metal anode.

[0007] The purpose of the present invention is achieved through the following technical solutions:

[0008] A method for preparing an alkali metal anode modified by an artificial SEI layer based on COF in-situ self-assembly comprises the following steps:

[0009] S1. Preparation of COF precursor solution A: mixing COF precursor monomer A and an organic solvent to obtain COF precursor solution A;

[0010] S2, preparation of COF precursor solution B: mixing COF precursor monomer B and an organic solvent to obtain COF precursor solution B;

[0011] S3, alkali metal surface functionalization treatment: evenly coating the organic functionalized solvent C on the alkali metal surface to obtain a functionalized alkali metal surface;

[0012] S4. Preparation of an alkali metal anode modified based on a COF layer: uniformly coating the COF precursor solution A obtained in step S1 on the functionalized alkali metal surface described in S3, and after drying, obtaining an alkali metal surface treated with A; uniformly coating the COF precursor solution B described in step S2 on the alkali metal surface treated with A, and after drying, washing the alkali metal surface with an organic solvent, and then drying the modified anode at a low temperature to obtain an alkali metal anode modified based on an in-situ self-assembled artificial SEI layer of COF.

[0013] The COF precursor monomer A in step S1 is trialdehyde phloroglucinol, 2,5-dihydroxyterephthalaldehyde or squaric acid; the COF precursor monomer A used in the present invention is a synthetic organic monomer that can be made into COF, which should not only have the ability to form COF, but also must be completely dissolved in a suitable organic solvent to form a solution so that subsequent COF in situ synthesis can be carried out.

[0014] The mass concentration of the COF precursor monomer A in the COF precursor solution A in step S1 is 1%-50%. The inventors have found through a large number of experiments that when the concentration of the COF precursor monomer A is within the above range, the thickness of the final artificial COF SEI layer can be more appropriate, the alkali metal can be isolated from the electrolyte, and the alkali metal ion deposition can be uniformly induced.

[0015] The COF precursor monomer B in step S2 is melamine, tris(4-aminophenyl)amine or 2,4,6-tris(4-aminophenyl)-1,3,5-triazine. The COF precursor monomer B used in the present invention is a synthetic organic monomer that can be made into COF. It should not only have the ability to form COF, but also must be completely dissolved in a suitable organic solvent to form a solution for subsequent COF in-situ synthesis.

[0016] The mass concentration of the COF precursor monomer B in the COF precursor solution B in step S2 is 1%-50%. The inventors have found through a large number of experiments that when the concentration of the COF precursor monomer B is within the above range, the thickness of the final artificial COF SEI layer can be more appropriate, the alkali metal can be isolated from the electrolyte, and the alkali metal ion deposition can be uniformly induced.

[0017] In step S4, COF precursor monomer A and COF precursor monomer B contain functional groups that can react, such as aldehyde group and amine group, hydroxyl group and amine group, etc., and can spontaneously react under relatively mild conditions to form COF. The molar ratio of COF precursor monomer A to COF precursor monomer B is consistent with the molar ratio required for spontaneous reaction to form COF.

[0018] The organic solvents in steps S1, S2 and S4 are all dimethyl sulfoxide, N,N-dimethylacetamide, N,N-dimethylformamide or tetrahydrofuran.

[0019] The organic functionalized solvent C in step S3 is 3-aminopropyltriethoxysilane or N-aminoethyl-3-aminopropyltriethoxysilane.

[0020] The organic functionalized solvent C in step S3 is 0.1-20 μL / cm 2 The amount of organic functional solvent C can be evenly coated on the surface of the alkali metal. The organic functional solvent C can react with the COF precursor monomer A, and the reaction site is the anchoring site of the COF layer; the inventors have found through a large number of experiments that when the amount of organic functional solvent C is within the above range, the COF layer of the final lithium metal negative electrode can evenly cover the alkali metal surface, and the ability to anchor the COF layer is relatively strong.

[0021] The molar ratio of the COF precursor monomer A in step S1 to the COF precursor monomer B in step S2 is 1:0.1-10. It should be noted that the molar concentrations of the COF precursor monomer A and the COF precursor monomer B correspond to each other and increase or decrease at the same time during the reaction.

[0022] The alkali metal surface is functionalized using an organic functionalized solvent C, which can react with the COF precursor monomer A to serve as an anchoring point between the COF and the alkali metal surface.

[0023] The low temperature drying in step S4 is carried out at a temperature of 30-160° C. When the electrode is modified by low temperature drying, the temperature should be controlled to have no effect on the anchoring point between the alkali metal and the COF layer.

[0024] The present invention adopts the above method, and the COF precursor is added step by step when modifying the anode. After the COF layer is formed, the COF precursor is cleaned and removed. Since the organic functionalized anode surface produces specific anchoring points, the COF layer will be firmly fixed on the anode surface and will not fall off. The in-situ synthesis of the COF layer not only uniformly induces the deposition of alkali metal ions and inhibits the growth of dendrites, but also increases the corresponding Young's modulus. Compared with the prior art, the artificial COF SEI layer is used to hinder the direct contact between the alkali metal and the electrolyte, thereby preparing an ultra-long, stable, dendrite-free alkali metal negative electrode.

[0025] The inventors have found through a large number of experiments that only when the mass concentration of the COF precursor monomer is within the above range, can the final artificial COF SEI layer be better for preparing an ultra-long, stable, dendrite-free alkali metal negative electrode, thereby having a better deposition effect on alkali metal ions; if the mass concentration of the COF precursor monomer A or B is less than 1%, the COF precursor monomer mixed solution is too dilute, resulting in the inability of the liquid to evenly cover the alkali metal surface, resulting in the inability of the subsequent COF layer to evenly cover the alkali metal surface; and when the mass concentration of the COF precursor monomer A or B is greater than 50%, the thickness of the COF layer finally prepared is too large, so that the COF layer is more on the alkali metal surface, which is easy to fall off, and the performance of the alkali metal negative electrode is greatly reduced.

[0026] The inventors also found that only when the amount of the organic functionalized solvent C is within the above range, the final artificial COF SEI layer can prepare an ultra-long stable, dendrite-free alkali metal negative electrode with better effect, thereby having a better deposition effect on alkali metal ions; if the amount of the organic functionalized solvent C is less than 0.1 μL / cm 2 , which results in the inability of the organic functional solvent C to evenly cover the alkali metal surface, and the COF anchoring points are too few, resulting in the inability of the subsequent COF layer to evenly cover the alkali metal surface; and the amount of organic functional solvent C is >20μL / cm 2 When the thickness of the organic functionalized solvent C layer is too large, the polarity is large, and the performance of the alkali metal negative electrode is greatly reduced.

[0027] The inventors also found that when the molar ratio of the COF precursor monomer A to the COF precursor monomer B is 1:0.1-10, the final artificial COF SEI layer not only has the effect of inducing alkali metal ion deposition, but also has a good Young's modulus; when the amount of COF precursor monomer A added is too small, the COF layer in the system is too thin, resulting in the final prepared artificial COF SEI layer having a very thin surface, which may not completely cover the alkali metal surface, and a poor Young's modulus; and when the amount of COF precursor monomer A added is too much, there is a layer of COF precursor monomer A between the alkali metal surface COF layer and the alkali metal surface, so that the COF layer is easy to fall off, affecting the performance of the alkali metal negative electrode.

[0028] In the preparation process of the alkali metal anode modified by the in-situ self-assembled artificial SEI layer of COF in the present invention, the limitation of the above parameters is very important. Each link is closely linked and directly affects the performance of the final ultra-long stable, dendrite-free lithium metal negative electrode.

[0029] An alkali metal anode modified by an artificial SEI layer based on COF in-situ self-assembly prepared by the above preparation method.

[0030] The above-mentioned COF-based in-situ self-assembled artificial SEI layer modified alkali metal anode is used in lithium batteries, sodium batteries and potassium batteries.

[0031] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0032] (1) The alkali metal anode modified by the COF in-situ self-assembled artificial SEI layer prepared by the present invention can avoid direct contact between the electrolyte and the alkali metal. The COF layer in the artificial EIS layer is evenly distributed, which can effectively and efficiently induce uniform deposition of alkali metal ions and inhibit the growth of dendrites.

[0033] (2) The COF layer on the modified alkali metal anode prepared by the preparation method of the present invention has a sufficiently large specific surface area-volume ratio and porosity, a complete alkali metal ion migration channel, and a good alkali metal ion migration rate.

[0034] (3) The preparation method of the present invention is simple. The COF layer is synthesized in situ to make the alkali metal surface have a rich porous structure, so that a large amount of COF is exposed evenly on the alkali metal surface, providing a rich pore structure for the migration of alkali metal ions, and inducing the uniform deposition of alkali metal ions, inhibiting the growth of dendrites. At the same time, the in situ grown COF layer has a good Young's modulus, overcoming the problem of volume expansion of existing alkali metal negative electrodes. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1The symmetric battery assembled based on the COF in-situ self-assembled artificial SEI layer modified alkali metal anode prepared in Example 1 was -2 , 1mAh·cm -2 Time-lapse potential effect diagram. DETAILED DESCRIPTION

[0036] The present invention is further described in detail below in conjunction with embodiments and drawings, but the embodiments of the present invention are not limited thereto.

[0037] Example 1

[0038] The method for preparing an alkali metal anode modified by an artificial SEI layer based on COF in-situ self-assembly described in this embodiment comprises the following steps:

[0039] S1. Preparation of a COF precursor trialdehyde phloroglucinol solution: 16.8 mg (0.08 mmol) of trialdehyde phloroglucinol was mixed with 100 mL of DMSO and stirred to obtain a COF precursor trialdehyde phloroglucinol solution;

[0040] S2. Preparation of COF precursor 2,4,6-tris(4-aminophenyl)-1,3,5-triazine solution: 28.32 mg (0.08 mmol) of 2,4,6-tris(4-aminophenyl)-1,3,5-triazine was mixed with 100 mL of DMSO and stirred to obtain a COF precursor 2,4,6-tris(4-aminophenyl)-1,3,5-triazine solution;

[0041] S3. Lithium metal surface functionalization treatment: Take the organic functional solvent 3-aminopropyltriethoxysilane at 8 μL / cm 2 Uniformly coating the lithium metal surface to aminate the lithium metal surface and obtain a functionalized lithium metal surface;

[0042] S4. Preparation of a lithium metal anode modified based on a COF layer: 8 μL of the COF precursor trialdehyde phloroglucinol solution described in step S1 is evenly coated on the functionalized lithium metal surface described in S3, and after it is dried, a trialdehyde phloroglucinol-treated lithium metal surface is obtained; 8 μL of the COF precursor 2,4,6-tris(4-aminophenyl)-1,3,5-triazine solution described in step S2 is evenly coated on the trialdehyde phloroglucinol-treated lithium metal surface, and after it is dried, the lithium metal surface is cleaned with DMSO, and then the modified anode is dried at low temperature to obtain an alkali metal anode modified based on an in situ self-assembled artificial SEI layer of COF.

[0043] Example 2

[0044] The difference between this embodiment and embodiment 1 is that in step S1, the COF precursor solution A is a COF precursor terephthalaldehyde solution, and the preparation method of the precursor solution is: 15.84 mg of terephthalaldehyde (dissolved in THF) is added to 100 mL of THF, and stirred for 3 hours to obtain a terephthalaldehyde solution; the remaining steps are consistent with embodiment 1.

[0045] Example 3

[0046] The only difference between this embodiment and embodiment 1 is that in step S2, the COF precursor solution B is a COF precursor melamine-based solution, and the preparation method of the precursor solution is: 10.08 mg of melamine (0.08 mmol) is added to 100 mL of DMSO, and stirred for 3 hours to obtain a melamine solution; the remaining steps are consistent with embodiment 1.

[0047] Example 4

[0048] The difference between this embodiment and embodiment 1 is that in step S3, the organic functionalized solvent is N-aminoethyl-3-aminopropyltriethoxysilane solution; the remaining steps are consistent with embodiment 1.

[0049] Example 5

[0050] The difference between this embodiment and embodiment 1 is that in step S1, the mass of trialdehyde phloroglucinol added is 0.168 mg, and the other steps are consistent with embodiment 1.

[0051] Example 6

[0052] The difference between this embodiment and embodiment 1 is that in step S1, the mass of trialdehyde phloroglucinol added is 1.68 mg, and the other steps are consistent with embodiment 1.

[0053] Example 7

[0054] The difference between this embodiment and embodiment 1 is that in step S1, the mass of trialdehyde phloroglucinol added is 84 mg, and the other steps are consistent with embodiment 1.

[0055] Example 8

[0056] The only difference between this embodiment and embodiment 1 is that in step S2, the mass of 2,4,6-tris(4-aminophenyl)-1,3,5-triazine added is 0.2832 mg, and the remaining steps are consistent with embodiment 1.

[0057] Example 9

[0058] The difference between this embodiment and embodiment 1 is that in step S2, the mass of 2,4,6-tris(4-aminophenyl)-1,3,5-triazine added is 2.832 mg, and the remaining steps are consistent with embodiment 1.

[0059] Example 10

[0060] The difference between this embodiment and embodiment 1 is that in step S2, the mass of 2,4,6-tris(4-aminophenyl)-1,3,5-triazine added is 141.6 mg, and the remaining steps are consistent with embodiment 1.

[0061] Embodiment 11

[0062] The difference between this embodiment and embodiment 1 is that in step S3, 2 μL of the organic functional solvent 3-aminopropyltriethoxysilane is evenly coated on the surface of the lithium metal, and the remaining steps are consistent with embodiment 1.

[0063] Example 12

[0064] The difference between this embodiment and embodiment 1 is that in step S3, 4 μL of the organic functional solvent 3-aminopropyltriethoxysilane is evenly coated on the surface of the lithium metal, and the remaining steps are consistent with embodiment 1.

[0065] Embodiment 13

[0066] The difference between this embodiment and embodiment 1 is that in step S3, 16 μL of the organic functional solvent 3-aminopropyltriethoxysilane is evenly coated on the surface of the lithium metal, and the remaining steps are consistent with embodiment 1.

[0067] Comparative Example 1

[0068] The difference between this comparative example and Example 1 is that in step S1, the mass of trialdehyde phloroglucinol added is 0.0168 mg, and the other steps are consistent with Example 1.

[0069] Comparative Example 2

[0070] The difference between this comparative example and Example 1 is that in step S1, the mass of trialdehyde phloroglucinol added is 0.0084 mg, and the other steps are consistent with Example 1.

[0071] Comparative Example 3

[0072] The difference between this comparative example and Example 1 is that in step S1, the mass of trialdehyde phloroglucinol added is 168 g, and the other steps are consistent with Example 1.

[0073] Comparative Example 4

[0074] The difference between this comparative example and Example 1 is that in step S1, the mass of trialdehyde phloroglucinol added is 1680 g, and the other steps are consistent with Example 1.

[0075] Comparative Example 5

[0076] The difference between this comparative example and Example 1 is that in step S2, the mass of 2,4,6-tris(4-aminophenyl)-1,3,5-triazine added is 0.028 mg, and the remaining steps are consistent with Example 1.

[0077] Comparative Example 6

[0078] The difference between this comparative example and Example 1 is that in step S2, the mass of 2,4,6-tris(4-aminophenyl)-1,3,5-triazine added is 0.14 mg, and the remaining steps are consistent with Example 1.

[0079] Comparative Example 7

[0080] The only difference between this embodiment and embodiment 1 is that in step S2, the mass of 2,4,6-tris(4-aminophenyl)-1,3,5-triazine added is 283.2 g, and the remaining steps are consistent with embodiment 1.

[0081] Comparative Example 8

[0082] The only difference between this embodiment and embodiment 1 is that in step S2, the mass of 2,4,6-tris(4-aminophenyl)-1,3,5-triazine added is 2832 g, and the remaining steps are consistent with embodiment 1.

[0083] Comparative Example 9

[0084] The difference between this comparative example and Example 1 is that in step S3, 0.02 μL of the organic functional solvent 3-aminopropyltriethoxysilane is uniformly coated on the surface of the lithium metal, and the remaining steps are consistent with Example 1.

[0085] Comparative Example 10

[0086] The difference between this comparative example and Example 1 is that in step S3, 0.002 μL of the organic functional solvent 3-aminopropyltriethoxysilane is uniformly coated on the surface of the lithium metal, and the remaining steps are consistent with Example 1.

[0087] Comparative Example 11

[0088] The difference between this comparative example and Example 1 is that in step S3, 64 μL of the organic functional solvent 3-aminopropyltriethoxysilane is evenly coated on the surface of the lithium metal, and the remaining steps are consistent with Example 1.

[0089] Comparative Example 12

[0090] The difference between this comparative example and Example 1 is that in step S3, 128 μL of the organic functional solvent 3-aminopropyltriethoxysilane is evenly coated on the surface of the lithium metal, and the remaining steps are consistent with Example 1.

[0091] Experimental Example 1

[0092] The COF in-situ self-assembled artificial SEI layer modified alkali metal anode prepared in the above embodiments and comparative examples was assembled into a battery for testing. Before assembling the battery, the purchased battery shell assembly was cleaned. The positive and negative electrode shells, springs, gaskets and cut diaphragms were washed twice in analytical pure ethanol, placed in an oven and completely dried, and then placed in a glove box for standby use. When assembling the battery, first place the prepared COF@Li electrode in the center of the positive electrode shell, drip a certain amount of electrolyte, fix the electrode at the positive electrode shell by the tension of the electrolyte, then place the Clgard2400 diaphragm (Ф=19mm) and drip a certain amount of electrolyte to ensure that both sides of the diaphragm are completely infiltrated by the electrolyte. Then place the negative electrode sheet corresponding to the center of the diaphragm, and stack the gasket, springs and negative electrode shell. Finally, use plastic tweezers to place the assembled battery under the sealing machine for stamping and sealing. If there is excess electrolyte, it can be wiped off with dust-free paper to ensure the success rate of fresh batteries. The prepared symmetric battery was charged at a constant current of 1 mA / cm 2 , 5mA / cm 2 At a current density of , deposition / stripping is performed with a fixed charge and discharge time to test the symmetrical battery; and rate tests are performed on currents of different sizes to finally obtain the time-voltage curve of the long-term cycle of the symmetrical battery.

[0093] Figure 1 The alkali metal anode modified by the artificial SEI layer based on COF in situ self-assembly obtained in Example 1 was 1 mA·cm -2 、1mAh·cm -2 Schematic diagram of overpotential under current density. Figure 1 It can be seen that the alkali metal anode modified by the COF in-situ self-assembled artificial SEI layer obtained in the present invention has the characteristics of good cycle stability and small overpotential.

[0094] Other Comparative Examples We observed through an in-situ optical microscope (LW750LJT) that in Comparative Examples 1 and 2, since the mass ratio of COF precursor A is not within the protection scope of the present invention, the COF yield is too low, and the alkali metal surface is not completely covered with the COF layer; in Comparative Examples 3 and 4, since the mass ratio of COF precursor A is not within the protection scope of the present invention, we observed the cross-section of the alkali metal composite COF through an in-situ optical microscope (LW750LJT), and it can be observed that the COF precursor A layer is too thick, making the COF layer on the alkali metal surface easy to fall off; similarly, we observed through an in-situ optical microscope (LW750LJT) that in Comparative Examples 5 and 6, since the mass ratio of COF precursor B is not within the protection scope of the present invention, Protection range, resulting in too low COF yield, the alkali metal surface is not completely covered with the COF layer; in comparative examples 7 and 8, since the mass ratio of COF precursor B is not within the protection range of the present invention, the COF precursor B layer is too thick, and the alkali metal surface polarization is large; and through in situ optical microscopy (LW750LJT) observation, due to the content ratio of the organic functionalized solvent C is not within the protection range of the present invention, the alkali metal surface is not fully functionalized, the anchoring points of the COF layer are reduced, and the COF layer is easy to fall off; in comparative examples 11 and 12, since the content ratio of the organic functionalized solvent C is not within the range provided by the present invention, the functionalized layer on the alkali metal surface is too thick, and polarization occurs on the alkali metal surface.

[0095] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principles of the present invention shall be equivalent replacement methods and shall be included in the protection scope of the present invention.

Claims

1. A method for preparing an alkali metal anode modified by an artificial SEI layer based on COF in situ self-assembly, characterized in that The steps include: S1. Preparation of COF precursor solution A: mixing COF precursor monomer A and an organic solvent to obtain COF precursor solution A; S2, preparation of COF precursor solution B: mixing COF precursor monomer B and an organic solvent to obtain COF precursor solution B; S3, alkali metal surface functionalization treatment: evenly coating the organic functionalized solvent C on the alkali metal surface to obtain a functionalized alkali metal surface; S4. Preparation of an alkali metal anode modified based on a COF layer: uniformly coating the COF precursor solution A obtained in step S1 on the functionalized alkali metal surface described in S3, and after drying, obtaining an alkali metal surface treated with A; uniformly coating the COF precursor solution B described in step S2 on the alkali metal surface treated with A, and after drying, washing the alkali metal surface with an organic solvent, and then drying the modified anode at a low temperature to obtain an alkali metal anode modified based on an in-situ self-assembled artificial SEI layer of COF.

2. The method for preparing an alkali metal anode modified by an artificial SEI layer based on COF in situ self-assembly according to claim 1, characterized in that: In step S1, the COF precursor monomer A is trialdehyde phloroglucinol, 2,5-dihydroxyterephthalaldehyde or squaric acid; the mass concentration of the COF precursor monomer A in the COF precursor solution A is 1%-50%.

3. The method for preparing an alkali metal anode modified by an artificial SEI layer based on COF in-situ self-assembly according to claim 1, characterized in that: In step S2, the COF precursor monomer B is melamine, tris(4-aminophenyl)amine or 2,4,6-tris(4-aminophenyl)-1,3,5-triazine; and the mass concentration of the COF precursor monomer B in the COF precursor solution B is 1%-50%.

4. The method for preparing an alkali metal anode modified by an artificial SEI layer based on COF in-situ self-assembly according to claim 1, characterized in that: The organic solvents in steps S1, S2 and S4 are all dimethyl sulfoxide, N,N-dimethylacetamide, N,N-dimethylformamide or tetrahydrofuran.

5. The method for preparing an alkali metal anode modified by an artificial SEI layer based on COF in-situ self-assembly according to claim 1, characterized in that: The organic functionalized solvent C in step S3 is 3-aminopropyltriethoxysilane or N-aminoethyl-3-aminopropyltriethoxysilane.

6. The method for preparing an alkali metal anode modified by an artificial SEI layer based on COF in-situ self-assembly according to claim 1, characterized in that: The organic functionalized solvent C in step S3 is 0.1-20 μL / cm 2 The amount is evenly coated on the surface of the alkali metal.

7. The method for preparing an alkali metal anode modified by an artificial SEI layer based on COF in-situ self-assembly according to claim 1, characterized in that: The molar ratio of the COF precursor monomer A in step S1 to the COF precursor monomer B in step S2 is 1:0.1-10.

8. The method for preparing an alkali metal anode modified by an artificial SEI layer based on COF in-situ self-assembly according to claim 1, characterized in that: The low temperature drying in step S4 is carried out at a temperature of 30-160°C.

9. An alkali metal anode modified by an artificial SEI layer based on COF in situ self-assembly prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the alkali metal anode modified by the COF in-situ self-assembled artificial SEI layer according to claim 9 in lithium batteries, sodium batteries and potassium batteries.

Citation Information

Patent Citations

  • Covalent organic framework / graphene compound organic material, as well as preparation method and application thereof in lithium / sodium ionic battery anode materials

    CN109524652A

  • Self-propagating alloying lithium negative electrode and preparation method thereof

    CN114141992A

  • Porous and conductive membrane for lithium-sulfur battery, method for manufacturing the same, and lithium-sulfur battery comprising the same

    KR1020170108496A

  • Hybrid lithium anode electrode layer and lithium-ion battery containing same

    US20190044137A1

  • Energy storage device, lithium growth control layer therefor, and electrode structure

    WO2022080767A1

Cited By

  • Preparation method of Mg-CO2 battery catalyst material

    CN120581605A